Analysis of Factors Influencing Consumer Behavior and Repurchase Decisions of Street Food Vendors in Garut Regency - Vida Ayu Sahara; Irfan Nabhani; Minto Yuwono (Entrepreneurship Faculty, Universitas Garut, 2025)
This study aims to analyze the influence of price, vendor image, location, physical environment, and perceived nutritional value on repurchase decisions among consumers of street food vendors in Garut Regency. The increasing popularity of street food consumption highlights the importance of understanding the factors that influence consumer loyalty and repeat purchase behavior. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 150 respondents who are consumers of street food across various areas in Garut Regency. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS software. The results indicate that price, vendor image, physical environment, and perceived nutritional value have a positive and significant effect on repurchase decisions, while location does not show a significant influence. Among the five factors, vendor image and perceived nutritional value have the most dominant impact on consumers’ decisions to repurchase food from street vendors. These findings provide important implications for street food entrepreneurs to consider pricing strategies, improve business image, choose strategic locations, maintain the physical environment of their stalls, and provide clear information about the nutritional value of their products in order to increase customer satisfaction and loyalty.